Structural and dynamical properties of polyethylenimine in explicit water at different protonation states: a molecular dynamics study - Choudhury, Chandan Kumar; Roy, Sudip (Soft Matter, 2013)
PEI is a pH sensitive polymer which acts as a proton sponge in acidic conditions. Despite many experimental and theoretical efforts, a fundamental understanding of the structure and dynamics of linear PEI chains on the atomistic level at different protonation states in dilute solutions remains a topic of discussion. This report analyses the structural properties of PEI at different protonation states, which are representative of different pH, using all atomistic molecular dynamic simulations. The structural properties revealed that the polymer at high pH (basic medium) is highly coiled, while at low pH (strong acidic conditions) the chains are elongated. We studied the dynamics and ordering of water molecules that are part of the solvation shells of the PEI chains at different protonation states. We observe that the water molecules are ordered along the polymer backbone for a completely protonated PEI chain (i.e. in the case of acidic pH) and hop to the neighbouring solvation shell. The residence time and the self-diffusion of water molecules in the solvation shells and their activation barriers were also calculated and analysed further. We concluded the study by correlating the solvation shell water dynamics and the structure of the PEI chain at different protonation states.